dylan_shadowlocke
New member
- Joined
- Sep 21, 2015
- Messages
- 3
In a previous question in my text book, I solved Y=f(x)+2 which is the same as Y=Y+2 so that very simply moved the whole graph up by 2.
I've been trying to solve this very simple equation, which i already have the answer to in my text book. I just don't understand it.
For the graph where f(x) is basically equal to y, and given the following points (x=2, f(x)=-1), (x=1, f(x)=1), (x=-1, f(x)=1), (x=-2, f(x)=-1)
How do I calculate y=f(X+2) ?
I know the "rule" is that i would move the entire graphed figure to the left, but I can't move past this until I understand a real math equation that will justify this so called "rule".
I've been ripping my hair out for hours over this!
Please help!
I've been trying to solve this very simple equation, which i already have the answer to in my text book. I just don't understand it.
For the graph where f(x) is basically equal to y, and given the following points (x=2, f(x)=-1), (x=1, f(x)=1), (x=-1, f(x)=1), (x=-2, f(x)=-1)
How do I calculate y=f(X+2) ?
I know the "rule" is that i would move the entire graphed figure to the left, but I can't move past this until I understand a real math equation that will justify this so called "rule".
I've been ripping my hair out for hours over this!
Please help!